RÉGIMEN PROBATORIO EN EL NUEVO CÓDIGO DE PROCEDIMIENTO PENAL (Decreto 50 de 1987) - Suarez Hernández, Daniel (Revistas ICDP, 2015)
RÉGIMEN PROBATORIO EN EL NUEVO CÓDIGO DE PROCEDIMIENTO PENAL (Decreto 50 de 1987)